Simulação numérica do escoamento particulado para o preenchimento de canal fraturado - De Lai, Fernando César (2013)
During the drilling process, the fluid loss to formation is one of the most important players that affect the productivity of the well. When combined with high pressure gradients at the wellbore-reservoir interface, fractures may eventually magnify the invasion phenomenon. These phenomena, when not predicted, must be controlled to restore the wellbore circulation. In this work, the fluid invasion is managed by injecting solid particles with the drilling fluid to obturate the fracture. The numerical simulation of the problem here investigated is divided in two parts, concerning the type of flow in the channel: monophase fluid flow, to analyze the invasion phenomenon and twophase flow (fluid and particles), to filling process of the fracture with particulated material. The mathematical formulation and numerical modeling are represented via an Euler-Lagrange approach. Coupled solution of discrete (particles) and continuum (fluid) phases is performed by combining the models Dense Discrete Phase Model (DDPM) and Discrete Element Method (DEM) available in ANSYS FLUENT. The filling of the fractures is characterized by analyzing the injection time (in the channel) and the format of the fixed bed (in the fracture) of the particles. This characterization is obtained by the variation of the main parameters for the particles injection that influence the concentration of particles within the channel. The results show the effect of varying the concentration of the solid particle phase for different monitoring parameters. The main parameters are the fluid flow rate through the outlet of the fracture the pressure of the mixture in the inlet of the channel and the concentration of particles injected into the channel.